Learning from Fables: Moral Values in Three Selected English Stories - Abrar, Mukhlash (Dinamika Ilmu, 2016)
Fable is not just a fun story, but more than that, it has moral lesson(s) inside of the storyline. This research tries to portray ethic value(s) in three selected English fable stories as well as to let the readers know that they can learn something from the fables. With this study, the researcher also correlated the value(s) to real life and Islamic views. To achieve the research objectives, the researcher employed qualitative research design with descriptive analysis as an attempt to provide an in-depth and comprehensive explanation of the data. The data of this study, gotten from the researcherâs random survey on Primary and Junior High Schools students on January âJune 2015, are three selected English fable stories entitled âThe Rabbit and the Turtle, The Fox and the Goat, and The Monkey and the Crocodileâ. The results indicate that each fable has, at least, a moral lesson in its narrative, among others: Never underestimate the weakest opponent, Never give up is the key of success, Think first before doing an action, Being smart helps better in life, and Trust is the basis of relationship.